Technical and Vocational Education and Training for Producing Graduates with Necessary Skills on Demand of Labour Market: The Moderating Role of Labour Market Information - Kaula Stephen (MASI Mandiri Edukasi, 2023)
This study analyzed the effects of technical and vocational education and training in acquiring graduates with the necessary skills that are labor market on demand. This analysis came following many graduates completing TVET college studies but finding they are not conforming to the skills a labor market is in demand with. To address this gap, the study used quantitative research approaches. While the research design was explanatory, the sampling technique was simple random sampling from a population of 3000 unit of analysis: students, graduates, tutors, and management staff from 3 selected NACTVET colleges, and 254 samples of respondents was obtained. Moreover, data collection from the sample extracted used a questionnaire. Before actual data analysis, a pilot survey, data cleaning, and factor analysis were conducted. The actual data analysis employed multiple linear regression from which the results were:-TVET-theoretical, practical, and behavioral attitudinal education found to be positively and significantly related to the production of resourceful graduates if the labor market information is intruded in the model system. These analytical results suggest that education stakeholders, policymakers, and curriculum developers adopt the model this study introduced by calling for the moderation role of labor market information.